Respuesta :

Given:

[tex]f(x)=4x-7[/tex]

[tex]g(x)=4x[/tex]

To find:

The expression for f(f(x)).

Solution:

We need to find f(f(x)).

[tex]f(f(x))=f(4x-7)[/tex]                             [tex][\because f(x)=4x-7][/tex]

[tex]f(f(x))=4(4x-7)-7[/tex]                             [tex][\because f(x)=4x-7][/tex]

Using distributive property, we get

[tex]f(f(x))=4(4x)+4(-7)-7[/tex]

[tex]f(f(x))=16x-28-7[/tex]

[tex]f(f(x))=16x-35[/tex]

Therefore, the expression for f(f(x)) is [tex]f(f(x))=16x-35[/tex].